A study on the relationship between job characteristics and level of motivation among support staff UiTM Sabah / Nasiha Abdullah @ Jobit Layun, Naliza Solat and Prof. Madya Rosdiana Hj. Sukardi - Abdullah @ Jobit Layun, Nasiha; Solat, Naliza; Sukardi, Rosdiana (Research Management Institute (RMI), 2012)
The aim of this paper is to gain insight into job characteristics dimensions that enhance level of motivation among support staff in UiTM Sabah. Assessment was made whether support staffs job characteristics in higher educational institution, influence their level of motivation. Analysis was conducted to measure level of motivation among support staff categories and the types of job performed. This correlational study used disproportionate stratified random sampling technique. The data was collected by distributing survey questionnaires to 155 support staff and the questionnaires were analyzed using SPSS version 20.0. The results showed that job characteristics dimensions positively influence support staffs' level of motivation. Generally, UiTM Sabah support staff are moderately motivated and they are motivated with the extrinsic factors more than the intrinsic factors. The findings of this study are limited to the population of support staff ranging from Group Support Grade B, Grade C and Grade D in UiTM Sabah only. It is recommended that the top management provide more job enrichment as well as conduct more trainings and development programs for the benefit of the support staff. There is also an urgent need to revise the employees' job description in order to resolve task delegation's issue. The top management of UiTM Sabah may use these findings in attracting potential employees, retaining quality support staff and continuously motivating them.